Gender and Economic Opportunities in Poland : Has Transition Left Women Behind? - World Bank (Washington, DC, 2013)
The study addresses the most significant disparities in women's and men's access to economic opportunities and discusses the roots of inequalities in their socioeconomic and political contexts. In light of recent changes to the Polish Labor Code that were introduced to promote equal rights for women and men on the labor market, the authors have attempted to answer the question of legal discrimination regarding women and men in the labor market, the social insurance and family benefits system, and in the work and retirement benefits systems. Chapter 2 describes the roots of gender stereotypes and their impacts; chapter 3 describes the employment structure in Poland, taking into account gender differences; chapter 4 concentrates on the growth dynamics of self-employment among women and men in the transition period, and the characteristics of the Polish businesswomen; chapter 5 raises the question of the limits faced by women in their professional careers; chapter 6 shows to extent to which the retirement system in Poland reflects the difference between the status of women and men in the labor market and shows the roots of the lower status of professional women. Finally, chapter 7 shows how the status of women in rural areas is determined by the role that is attributed to them in the family, in the society, and in the traditional division of labor. The report concludes by providing a number of policy recommendations that may prove to be important instruments in eliminating gender disparities and building poverty reduction strategies.